Lifeworld interpretation of tinnitus. Issue 4 (24th June 2019) - Pryce, Helen; Shaw, Rachel
Abstract : Lifeworld-led care provides a route through which research and practice can navigate the 'biopsychosocial' allowing us to overcome the shortfalls of the medical model and enabling us to prioritise humanity in the care of people living with tinnitus. In this article, we sought to explore qualitative descriptions of life with tinnitus. We aimed to address the question 'what it is like to live with tinnitus?' In doing so we examined qualitative studies and provide suggestions about key themes that seem consistent. This is a narrative, thematic overview of the way lifeworld has been conceptualised and explored in tinnitus research.